Integrating science for water security governance - Kristen M. Whitney; Rebecca M. Peters; Anil Mishra; Annalise G. Blum; Perry C. Oddo; Kate A. Brauman; Angelica L. Gutierrez; John D. Bolten; Matthew J. McCarthy; Andrés Sánchez (Global Environmental Change, 2026)

Critical choices for nature assessment design in emerging environmental markets - S.J. Capon; J. Brazil-Boast; J.A. Fitzsimons; J. McDonald; S.M. Prober; R. Trebilco; I. Cresswell; J. Perry; M. Bachmann; J. Pittock; C. Hunter; T.J. Eyre (Environmental Development, 2026)

The northern California current on fire: consequences of a widespread and persistent anomalous pyrosome bloom - Richard D. Brodeur; Dylan G.E. Gomes; Douglas L. Draper; Elizabeth A. Daly; Samantha M. Zeman; Moira Galbraith; R. Ian Perry; James J. Ruzicka; Roxanne R. Robertson (Progress in Oceanography, 2026)

Cryptic coral reef microhabitats and the functional role of brittle stars in biogenic sediment generation - D. M. de Bakker; C. T. Perry; L. de Nooijer; A. J. Ramírez-Menéndez; J. E. Lloyd Newman; F. Hale; L. Alvarez-Filip (Coral Reefs, 2026)
Recent studies have highlighted the ecological importance of cryptic habitat space on coral reefs. These microhabitats, ranging from framework cavities to intra-branch space within marine macroalgae, can harbour diverse and ecologically relevant taxa. Here we show that brittle stars, ubiquitous across such cryptic habitats (reported densities exceeding 100 ind. m −2 ), represent an important, but previously neglected, source of skeletal sediment on reefs. Reef-derived carbonate sediment is generated by a range of reef biota and represents a critical geo-ecological process, contributing to reef structural development and vertical accretion via framework infilling, and the development and maintenance of lagoonal and shoreline habitats. Our sediment production estimates are based on skeletal carbonate content data for differently sized specimens of common brittle star morphotypes, combined with field-based density assessments from widespread microhabitat types (framework cavities, sub-rubble space and intra-algal skeletal branches) on Mexican Caribbean reefs. Resulting estimates suggest that brittle stars can make substantial contributions to reef sediment production (averaging 110 g m⁻ 2 yr⁻ 1 ; 95% CI 59–161). Spine-bearing taxa contribute disproportionately due to their high skeletal mass (> 6 g in large individuals) and high abundance (accounting for over 80% of sub-rubble populations). Resultant biogenic sediments are high-Mg calcite (15.6 ± 0.1 mol% MgCO₃) and predominantly disarticulate into fine to coarse-grained sand material (125 µm–2 mm). These findings highlight the underappreciated role of brittle stars in reef carbonate cycling. With many reef systems undergoing rapid changes in benthic ecology and microhabitat space availability, identifying and characterising links to biogenic sediment sources is central to understanding future reef sediment production regimes.

CRISPR Epigenome Editing of IL1R1 Expression of Neurons that Innervate the Temporomandibular Joint or Knee Causes Reduced Sensitization to Osteoarthritic Environment - Joshua D. Stover; Robby D. Bowles; Yenisel Cruz-Almeida; Robert M. Caudle; Kyle D. Allen; Armen Akopian; Benjamin Arenkiel; Basak Ayaz; Yangjin Bae; Bruna Balbino de Paula; Anita Bandrowski; Mario Danilo Boada; et al. (Annals of Biomedical Engineering, 2026)

Comparative efficacy of electrokinetic and static leaching for selective metal recovery and nutrient release from porphyry Cu tailings - Yujie Yan; Gawen R.T. Jenkin; Andrew P. Abbott; Alexandria Tanciongco; Carlo A. Arcilla; Cris Reven L. Gibaga; Daniel J. Smith; Djoan Kate Tungpalan; Jonathan E. Chambers; John Henry C. Gervasio; James Symons; Justine Perry T. Domingo; et al. (Chemical Engineering Journal, 2026)

Isolation and characterisation of cell wall polysaccharides from taewa (Māori potatoes; Solanum tuberosum L.) - Cara.A. Luiten; Simon F.R. Hinkley; Nick R. Roskruge; Saii A. Semese; Anne-Louise M. Heath; Tracy L. Perry; Nancy J. Rehrer; Ian M. Sims (Food Hydrocolloids, 2026)

Upstate Abundance, a Variety with Small Round White Tubers and Resistance to Lineage US-23 of Late Blight and Pathotypes Ro1 and Ro2 of the Golden Cyst Nematode - Walter S. De Jong; Xiaohong Wang; Donald E. Halseth; Robert L. Plaisted; Keith L. Perry; Xinshun Qu; Barbara J. Christ; Ken M. Paddock; Matthew Falise (American Journal of Potato Research, 2026)
Upstate Abundance is a fresh market white-fleshed potato cultivar with resistance to both pathotypes Ro1 and Ro2 of the golden cyst nematode ( Globodera rostochiensis ) as well as to late blight ( Phytophthora infestans ) lineage US-23. It was selected from a cross made at Cornell University in 2000 between the Cornell breeding clone NY121 and the fresh-market cultivar Jacqueline Lee and released by the New York Agricultural Experiment Station in 2017. The tubers are small and round with modestly-recessed eyes and smooth skin; total yield across 20 trials in New York and Pennsylvania averaged 36.6 Mg ha − 1 , with about half the yield in tubers less than 4.75 cm in diameter and most of the rest in tubers between 4.75 and 6.4 cm in diameter.

Passive environmental DNA (eDNA) sampling is effective for monitoring vessel biofouling in the Southern Ocean - Frances Perry; Justine D. Shaw; Phillip Cassey; Ashley Coutts; Patrick N. Lewis; Anna J. MacDonald; Andrea M. Polanowski; Jonathan S. Stark; Leonie Suter (Science of The Total Environment, 2026)

Bridging the Gap: Enhancing Prostate Cancer Survivorship and Advocacy Among Ethnically Diverse Black Men Through Community Town Halls - Motolani E. Ogunsanya; Ernest Kaninjing; Sara M. DeForge; Daniel J. Morton; Perry Cole; Patrick Beckford; Donald Reese; Thomas Mitchell; Everett Montgomery; Roland Odeleye; Erick Y. Miró-Rivera; Kaitlin Roberts; et al. (Journal of Cancer Education, 2025)
We present findings from town hall meetings held with ethnically diverse Black prostate cancer (CaP) survivors in 2022 and 2023. Four town halls (total participants, N = 265) focused on diagnosis, treatment, psychosocial support, and overall survivorship. Moderated by a long-term CaP survivor, each session featured a panel that included medical providers (urologic oncologists and clinical psychologists), as well as CaP survivors of American, Caribbean, and African origin and their spouses. Surveys captured demographic data, clinical information, CaP-specific details (for survivors only), and perceptions of the town halls. The meetings highlighted three interrelated themesinfluencing decision-making: access to comprehensive information, the strength of support networks, and the availability of culturally competent care. These town halls revealed important educational and support opportunities for ethnically diverse Black men with CaP, promoting informed decision-making throughout the cancer journey and improving quality of life while reducing decisional regret during survivorship.

Myeloid-specific tristetraprolin mitigates postsurgical incisional pain by suppressing proinflammatory responses - Abhishek Guha; Robert E. Sorge; Ying Si; Reed Smith; Sohail M. Baig; Mohammed Amir Husain; Stacie K. Totsch; Ava M. Piper; Perry J. Blackshear; Peter H. King (Inflammation Research, 2025)
Background Proinflammatory mediators including COX-2, IL-1β, IL-6, and TNF-α, play major roles in the initiation of postsurgical pain. Produced primarily by activated macrophages and microglia, these mediators drive hyperexcitation of nociceptors and promote peripheral and central pain sensitization. Post-transcriptional RNA regulation is a major control point for these mediators, centering around adenine- and uridine-rich elements (ARE) in the 3’ untranslated regions of their mRNA transcripts. The ARE governs RNA stability and translational efficiency through an interaction with ARE-specific RNA binding proteins (AUBP). Tristetraprolin (TTP) is an AUBP that promotes RNA degradation and translational silencing of these mediators to suppress inflammatory responses. Methods Mice with myeloid-specific TTP knockout or TTP knock-in underwent paw incision and were assessed for mechanical allodynia and thermal sensitivity. Molecular and cellular inflammatory responses were monitored at the site of incision, dorsal root ganglia (DRG) and lumbar spinal cord (L-SC) by qPCR, ELISA, immunohistochemistry and/or flow cytometry. Results TTP deletion exacerbated post-incisional allodynic pain in parallel with increased edema at the site of injury and delayed wound healing but without significant effects on thermal sensitivity. There was an increase in infiltrating macrophages at the incisional site, particularly at the dermal–epidermal junction, in parallel with a robust increase in proinflammatory/pronociceptive mediators. An enhanced inflammatory response was also detected in the circulation, ipsilateral DRG and L-SC which persisted through post-incisional day 7. Conversely, TTP knock-in mice showed attenuation of allodynic pain and inflammatory responses in skin, DRG, L-SC, and circulation. Conclusion TTP plays a critical role in mitigating postsurgical pain by tamping down peripheral, central and systemic inflammatory responses, thus identifying a new target and mechanism for future development of pain therapeutics.

Quantitative insights into the spatio‐temporal variation of Atlantic salmon ( Salmo salar ) biomass in a river catchment using eDNA metabarcoding - William Bernard Perry; Nigel Milner; Ifan Bryn Jâms; Mark de Bruyn; Steve J. Ormerod; Kristy Deiner; Holly M. Bik; Gary Carvalho; John Colbourne; Bernard Jack Cosby; Isabelle Durance; Simon Creer (Journal of Fish Biology, 2025)
Effective species conservation and management requires comprehensive biomonitoring, enhanced by combining traditional and newer methodologies, such as environmental DNA (eDNA) analyses. A seasonal pulse of spawning adult Atlantic salmon ( Salmo salar ) was detected by normalised eDNA 12S reads from metabarcoding, which facilitated estimation of spatial patterns in salmon biomass. A strong relationship was found between normalised reads in the lower section of the River Conwy (Wales, UK) and whole‐river adult biomass (estimated from rod catch data and a fish counter), explaining 61% of the variation in a linear regression. Moreover, the positive linear relationship between adult biomass and partial effect on normalised reads occurred after the biomass estimate exceeded 1500 kg, indicating a threshold where normalised reads become representative of biomass. The relationship observed between normalised reads and biomass, as well as the unique profiles of normalised reads at each of the sites, supports the hypothesis of limited eDNA transport among sampling sites that were 2–4 km apart. River pH showed a significant non‐linear relationship with normalised reads, with a peak in partial effect on normalised reads at pH 6.5. Partial effect on normalised reads also showed a positive linear relationship with flow (discharge), while also peaking at the highest average monthly air temperatures (14°C). These trends are contrary to what would be expected from eDNA decay, dilution or transport, demonstrating that metabarcoding is robust to such influences, reinforcing the interpretation of trends driven by Atlantic salmon ecology and physiology. For example, pH effects reflect beneficial conditions for eggs and perhaps habitat preference for spawners, flow effects reflect the annual return of salmon during higher flows which aid upstream migration, tributary entry and spawning, and, finally, temperature effects reflect higher metabolic rates and greater shedding of eDNA.

The University of West Florida campus ecosystem study: effects of persistent canopy openings on a chronically fire-excluded longleaf pine ecosystem - Frank S. Gilliam; Katherine M. Lundgren; Leo P. Young; Alexis J. Bjornstad; Caden M. Perry (Urban Ecosystems, 2025)

Estimating Spatially Explicit Survival and Mortality Risk From Telemetry Data With Thinned Point Process Models - Joseph M. Eisaguirre; Madeleine G. Lohman; Graham G. Frye; Heather E. Johnson; Thomas V. Riecke; Perry J. Williams (Ecology Letters, 2025)
Mortality risk for animals often varies spatially and can be linked to how animals use landscapes. While numerous studies collect telemetry data on animals, the focus is typically on the period when animals are alive, even though there is important information that could be gleaned about mortality risk. We introduce a thinned spatial point process (SPP) modelling framework that couples relative abundance and space use with a mortality process to formally treat the occurrence of mortality events across the landscape as a spatial process. We show how this model can be embedded in a hierarchical statistical framework and fit to telemetry data to make inferences about how spatial covariates drive both space use and mortality risk. We apply the method to two data sets to study the effects of roads and habitat on spatially explicit mortality risk: (1) VHF telemetry data collected for willow ptarmigan in Alaska, and (2) hourly GPS telemetry data collected for black bears in Colorado. These case studies demonstrate the applicability of this method for different species and data types, making it broadly useful in enabling inferences about the mechanisms influencing animal survival and spatial population processes while formally treating survival as a spatial process, especially as the development and implementation of joint analyses continue to progress.

Was extinction of New Zealand's avian megafauna an unavoidable consequence of human arrival? - Sean Tomlinson; Mark V. Lomolino; Jamie R. Wood; Atholl Anderson; George L.W. Perry; Janet M. Wilmshurst; Jeremy J. Austin; Damien A. Fordham (Science of The Total Environment, 2025)

Leaf Dry Matter Content Is Phylogenetically Conserved and Related to Environmental Conditions, Especially Wildfire Activity - Dachuan Dai; Dongli Yu; Wuchao Gao; George L. W. Perry; Adrian M. Paterson; Chengming You; Shixing Zhou; Zhenfeng Xu; Congde Huang; Dongyu Cao; Timothy J. Curran; Xinglei Cui (Ecology Letters, 2025)
Leaf dry matter content (LDMC) is an important determinant of plant flammability. Investigating global patterns of LDMC could provide insights into worldwide plant flammability patterns, informing wildfire management. We characterised global patterns of LDMC across 4074 species from 216 families, revealing that phylogenetic and environmental constraints influence LDMC. LDMC varied across growth forms and taxonomic groups, displaying phylogenetic niche conservatism. Temperature, precipitation, aridity index, soil total nitrogen content and wildfire activity affected LDMC, and the effect of wildfire activity was stronger than other environmental factors across species with postfire regeneration abilities. Such species had higher LDMC, and their LDMC was less phylogenetically conserved and more strongly associated with fire activity. Our results suggest that, although LDMC shows phylogenetic niche conservatism, LDMC is determined by environmental factors, especially wildfire activity. Wildfire has likely acted as a selective pressure towards high LDMC across species that persist through fire using postfire regeneration.

Intrinsic and environmental drivers of pairwise cohesion in wild Canis social groups - John F. Benson; David A. Keiter; Peter J. Mahoney; Benjamin L. Allen; Lee Allen; Francisco Álvares; Morgan L. Anderson; Shannon M. Barber‐Meyer; Adi Barocas; James C. Beasley; Linda Behrendorff; Jerrold L. Belant; et al. (Ecology, 2025)
Animals within social groups respond to costs and benefits of sociality by adjusting the proportion of time they spend in close proximity to other individuals in the group (cohesion). Variation in cohesion between individuals, in turn, shapes important group‐level processes such as subgroup formation and fission–fusion dynamics. Although critical to animal sociality, a comprehensive understanding of the factors influencing cohesion remains a gap in our knowledge of cooperative behavior in animals. We tracked 574 individuals from six species within the genus Canis in 15 countries on four continents with GPS telemetry to estimate the time that pairs of individuals within social groups spent in close proximity and test hypotheses regarding drivers of cohesion. Pairs of social canids ( Canis spp.) varied widely in the proportion of time they spent together (5%–100%) during seasonal monitoring periods relative to both intrinsic characteristics and environmental conditions. The majority of our data came from three species of wolves (gray wolves, eastern wolves, and red wolves) and coyotes. For these species, cohesion within social groups was greatest between breeding pairs and varied seasonally as the nature of cooperative activities changed relative to annual life history patterns. Across species, wolves were more cohesive than coyotes. For wolves, pairs were less cohesive in larger groups, and when suitable, small prey was present reflecting the constraints of food resources and intragroup competition on social associations. Pair cohesion in wolves declined with increased anthropogenic modification of the landscape and greater climatic variability, underscoring challenges for conserving social top predators in a changing world. We show that pairwise cohesion in social groups varies strongly both within and across Canis species, as individuals respond to changing ecological context defined by resources, competition, and anthropogenic disturbance. Our work highlights that cohesion is a highly plastic component of animal sociality that holds significant promise for elucidating ecological and evolutionary mechanisms underlying cooperative behavior.

Evaluating the coral microbiome during cryopreservation - Tori Jefferson; E. Michael Henley; Patrick M. Erwin; Claire Lager; Riley Perry; Darya Chernikhova; Matthew J. Powell-Palm; Blake Ushijima; Mary Hagedorn (Cryobiology, 2024)

Dust in the Critical Zone: North American case studies - J. Brahney; R.C. Heindel; T.E. Gill; G. Carling; J.M. González-Olalla; J. Hand; D.V. Mallia; J.S. Munroe; K. Perry; A.L. Putman; S.M. Skiles; B.R. Adams; et al. (Earth-Science Reviews, 2024)

Residual benefits of alum, gypsum, and magnesium sulfate amendments in reducing phosphorus losses to snowmelt runoff - Madelynn M. Perry; Darshani Kumaragamage; Douglas Goltz; Nora J. Casson; Inoka Amarakoon; Srimathie P. Indraratne (CATENA, 2024)

Back from the brink: Estimating daily and annual abundance of natural-origin salmon smolts from 30-years of mixed-origin capture-recapture data - Dalton J. Hance; John M. Plumb; Russell W. Perry; Kenneth F. Tiffan (Fisheries Research, 2024)

Three-dimensional imaging of martian glaciated terrain using Mars Reconnaissance Orbiter Shallow Radar (SHARAD) observations - Matthew R. Perry; Aaron T. Russell; Megan B. Russell; Frederick J. Foss; Frank C. Chuang; Gareth A. Morgan; Zachary M. Bain; Bruce A. Campbell; Nathaniel E. Putzig (Icarus, 2024)

Sustainable mining in tropical, biodiverse landscapes: Environmental challenges and opportunities in the archipelagic Philippines - Justine Perry T. Domingo; Gawen R.T. Jenkin; Laura Quick; Richard D. Williams; Karen A. Hudson-Edwards; Cecilia Tortajada; Patrick Byrne; Tom J. Coulthard; Jenielyn T. Padrones; Rich Crane; Cris Reven L. Gibaga; Grigorios Vasilopoulos; et al. (Journal of Cleaner Production, 2024)

Within-field extrapolation away from a soil moisture probe using freely available satellite imagery and weather data - R. G. V. Bramley; E. M. Perry; J. Richetti; A. F. Colaço; D. J. Mowat; C. E. M. Ratcliff; R. A. Lawes (Precision Agriculture, 2024)
Recognition of the importance of soil moisture information to the optimisation of water-limited dryland cereal production has led to Australian growers being encouraged to make use of soil moisture sensors. However, irrespective of the merits of different sensing technologies, only a small soil volume is sensed, raising questions as to the utility of such sensors in broadacre cropping, especially given spatial variability in soil water holding capacity. Here, using data collected from contrasting sites in South Australia and Western Australia over two seasons, during which either wheat or barley were grown, we describe a method for extrapolating soil moisture information away from the location of a probe using freely-available NDVI time series and weather data as covariates. Relationships between soil moisture probe data, cumulative NDVI (ΣNDVI), cumulative net precipitation (ΣNP) and seasonal growing degree days (GDD) were significant ( P < 0.0001). In turn, these could be used to predict soil moisture status for any location within a field on any date following crop emergence. However, differences in ΣNDVI between different within-field zones did not fully explain differences in the soil moisture from multiple sensors located in these zones, resulting in different calibrations being required for each sensor or zone and a relatively low accuracy of prediction of measured soil moisture (R 2 adj ~ 0.4–0.7) which may not be sufficient to support targeted agronomic decision-making. The results also suggest that at any location within a field, the range of variation in soil moisture status down the soil profile on any given date will present as greater than the spatial variation in soil moisture across the field on that date. Accordingly, we conclude that, in dryland cereal cropping, the major value in soil moisture sensors arises from an enhanced ability to compare seasons and to relate similarities and differences between seasons as a guide to decision-making.

Using parentage-based tagging to estimate survival of Chinook salmon fry in a large storage reservoir - Adam C. Pope; Tobias J. Kock; Russell W. Perry; Karen M. Cogliati; Kathleen G. O’Malley; Christina A. Murphy; Dalton J. Hance; Scott D. Fielding (Environmental Biology of Fishes, 2024)

Revealing the palaeoecology of silent taxa: selecting proxy species from associations in modern vegetation data - Jacqui M. M. Vanderhoorn; Janet M. Wilmshurst; Sarah J. Richardson; Thomas R. Etherington; George L. W. Perry (Journal of Biogeography, 2024)
Aim Species severely under‐represented in fossil pollen records leave gaps in interpretations and reconstructions of past vegetation. These ‘silent taxa’ leave little or no trace due to low pollen production, dispersal, preservation and taxonomic resolution. An approach for including them is through associating them with other species with reliable pollen representation. Here, we demonstrate a method for selecting such a proxy species for the Holocene using modern vegetation data. Location New Zealand. Taxon Beilschmiedia tawa (A.Cunn.) Benth. & Hook. F. ex Kirk (Lauraceae). Methods We used vegetation plot data to perform a pairwise co‐occurrence analysis of the New Zealand indigenous forest metacommunity to identify species with a strong positive association with Beilschmiedia tawa (tawa), a common tree severely under‐recorded in the pollen record. For those species, we then modelled their realised climatic niches to identify species with high niche overlap. We discuss how well those species could be interpreted from the Holocene fossil pollen record based on the representation of their pollen taxa. Results Knightia excelsa (rewarewa; Proteaceae) is a potential proxy for B. tawa in Holocene fossil pollen records, and other, range‐limited species may provide community‐specific proxies. We show combining resampling with sub‐sampling is a robust method for reducing the high false positive rate associated with large co‐occurrence analyses (1000+ sites) by limiting the sample size to 100 sites. Main Conclusions We show that the palaeoecology of silent taxa can be studied via proxy species, allowing their past distributions to be better understood. We highlight the importance of modelling many aspects of the realised niche to understand the usefulness and limitations of the silent–proxy association. Future research should focus on testing the underlying assumptions of the silent–proxy relationship so that models built on modern data can confidently be applied to palaeoecological data.

fNIRS is capable of distinguishing laterality of lower body contractions - Rob J. MacLennan; Jesus A. Hernandez-Sarabia; Shawn M. Reese; JoCarol E. Shields; Claire M. Smith; Katharina Stute; Jordyn Collyar; Alex A. Olmos; Tyler L. Danielson; Demi L. MacLennan; Jason I. Pagan; Ryan M. Girts; et al. (Experimental Brain Research, 2024)

A new approach to geostatistical synthesis of historical records reveals capuchin spatial responses to climate and demographic change - Odd T. Jacobson; Brendan J. Barrett; Susan E. Perry; Genevieve E. Finerty; Kate M. Tiedeman; Margaret C. Crofoot (Ecology Letters, 2024)
Recent proliferation of GPS technology has transformed animal movement research. Yet, time‐series data from this recent technology rarely span beyond a decade, constraining longitudinal research. Long‐term field sites hold valuable historic animal location records, including hand‐drawn maps and semantic descriptions. Here, we introduce a generalised workflow for converting such records into reliable location data to estimate home ranges, using 30 years of sleep‐site data from 11 white‐faced capuchin ( Cebus imitator ) groups in Costa Rica. Our findings illustrate that historic sleep locations can reliably recover home range size and geometry. We showcase the opportunity our approach presents to resolve open questions that can only be addressed with very long‐term data, examining how home ranges are affected by climate cycles and demographic change. We urge researchers to translate historical records into usable movement data before this knowledge is lost; it is essential to understanding how animals are responding to our changing world.

Ambient air pollution and rate of spontaneous abortion - Amelia K. Wesselink; Kipruto Kirwa; Perry Hystad; Joel D. Kaufman; Adam A. Szpiro; Mary D. Willis; David A. Savitz; Jonathan I. Levy; Kenneth J. Rothman; Ellen M. Mikkelsen; Anne Sofie Dam Laursen; Elizabeth E. Hatch; et al. (Environmental Research, 2024)

Digital strategies for nitrogen management in grain production systems: lessons from multi-method assessment using on-farm experimentation - A. F. Colaço; B. M. Whelan; R. G. V. Bramley; J. Richetti; M. Fajardo; A. C. McCarthy; E. M. Perry; A. Bender; S. Leo; G. J. Fitzgerald; R. A. Lawes (Precision Agriculture, 2024)
During the past few decades, a range of digital strategies for Nitrogen (N) management using various types of input data and recommendation frameworks have been developed. Despite much research, the benefits accrued from such technology have been equivocal. In this work, thirteen methods for mid-season N recommendations in cereal production systems were evaluated simultaneously, ranging from simple mass balance through to non-mechanistic approaches based on machine learning. To achieve this, an extensive field research program was implemented, comprising twenty-one N strip trials implemented in wheat and barley fields across Australia over four cropping seasons. A moving window regression approach was used to generate crop response functions to applied N and calculate economically optimal N rates along the length of the strips. The N recommendations made using various methods were assessed based on the error against the optimal rate and expected profitability. The root mean squared error of the recommendations ranged from 15 to 57 kg/ha. The best performing method was a data-driven empirical strategy in which a multivariate input to characterise field and season conditions was abundantly available and used to predict optimal N rates using machine learning. This was the only approach with potential to substantially outperform the existing farmer management, reducing the recommendation error from 42 to 15 kg/ha and improving profitability by up to A$47/ha. Despite being reliant on extensive historical databases, such a framework shows a promising pathway to drive production systems closer towards season- and site-specific economically optimum recommendations. Automated on-farm experimentation is a key enabler for building the necessary crop response databases to run empirical data-driven decision tools.

Observing change in pelagic animals as sampling methods shift: the case of Antarctic krill - Simeon L. Hill; Angus Atkinson; Javier A. Arata; Anna Belcher; Susan Bengtson Nash; Kim S. Bernard; Alison Cleary; John A. Conroy; Ryan Driscoll; Sophie Fielding; Hauke Flores; Jaume Forcada; et al. (Frontiers in Marine Science, 2024)
Understanding and managing the response of marine ecosystems to human pressures including climate change requires reliable large-scale and multi-decadal information on the state of key populations. These populations include the pelagic animals that support ecosystem services including carbon export and fisheries. The use of research vessels to collect information using scientific nets and acoustics is being replaced with technologies such as autonomous moorings, gliders, and meta-genetics. Paradoxically, these newer methods sample pelagic populations at ever-smaller spatial scales, and ecological change might go undetected in the time needed to build up large-scale, long time series. These global-scale issues are epitomised by Antarctic krill ( Euphausia superba ), which is concentrated in rapidly warming areas, exports substantial quantities of carbon and supports an expanding fishery, but opinion is divided on how resilient their stocks are to climatic change. Based on a workshop of 137 krill experts we identify the challenges of observing climate change impacts with shifting sampling methods and suggest three tractable solutions. These are to: improve overlap and calibration of new with traditional methods; improve communication to harmonise, link and scale up the capacity of new but localised sampling programs; and expand opportunities from other research platforms and data sources, including the fishing industry. Contrasting evidence for both change and stability in krill stocks illustrates how the risks of false negative and false positive diagnoses of change are related to the temporal and spatial scale of sampling. Given the uncertainty about how krill are responding to rapid warming we recommend a shift towards a fishery management approach that prioritises monitoring of stock status and can adapt to variability and change.

A new multispectral index for canopy nitrogen concentration applicable across growth stages in ryegrass and barley - Manish Kumar Patel; Dongryeol Ryu; Andrew W. Western; Glenn J. Fitzgerald; Eileen M. Perry; Helen Suter; Iain M. Young (Precision Agriculture, 2024)
Accurately monitoring Canopy Nitrogen Concentration (CNC) is a prerequisite for precision nitrogen (N) fertiliser management at the farm scale with carbon and N budgeting across the landscape and ecosystems. While many spectral indices have been proposed for CNC monitoring, their applicability and accuracy are often adversely affected by confounding factors such as aboveground biomass (AGB), crop type, growth stages, and environmental conditions, limiting their broader application and adoption; with AGB being one of the most dominant signals and confounding factors at canopy scale. The confounding effect can become more challenging as AGB is also physiologically linked with CNC across the growth stages. Additionally, the interplay between index form, selection of optimal wavebands and their bandwidths remains poorly understood for CNC index design. This study proposes robust and cost-effective 2- and 4-waveband multispectral (MS) CNC indices applicable across a wide range of crop conditions. We collected 449 canopy reflectance spectra (400–980 nm) together with corresponding CNC and AGB measurements across four growth stages of ryegrass (winter and summer), and five growth stages of barley (winter-spring) in Victoria, Australia, in 2018 and 2019. All possible waveband (400–980 nm) combinations revealed that the best combination varied between seasons and crop types. However, the visible spectrum, particularly the blue region, presented high and consistent performance. Bandwidths of 10–40 nm outperformed either very narrow (2 nm) or very broad bandwidths (80 nm). The newly developed 2-waveband index (416 and 442 nm with 10-nm bandwidth; R 2 = 0.75 and NRMSE = 0.2) and 4-waveband index (512, 440, 414 and 588 nm with 40-nm bandwidth; R 2 = 0.81 and NRMSE = 0.17) exhibited the best performance, while validation with an independent dataset (from a different growing period to those used in the model development) obtained NRMSE values of 0.25 and 0.24, respectively. The 4-waveband index provides enhanced performance and permits use of broader bandwidths than its 2-waveband counterpart.

Brodie, a Dual-Purpose Chipping and Tablestock Variety with Resistance to Pathotypes Ro1 and Ro2 of the Golden Cyst Nematode and Partial Resistance to Pathotype Pa2/3 of the Pale Cyst Nematode - Walter S. De Jong; Xiaohong Wang; Donald E. Halseth; Robert L. Plaisted; Keith L. Perry; Xinshun Qu; Ken M. Paddock; Matthew Falise; Louise-Marie Dandurand; Barbara J. Christ; Gregory A. Porter (American Journal of Potato Research, 2024)

Organophosphate ester flame retardants and plasticizers in house dust and mental health outcomes among Canadian mothers: A nested prospective cohort study in CHILD - Stephanie A. Foster; Molly L. Kile; Perry Hystad; Miriam L. Diamond; Liisa M. Jantunen; Piush J. Mandhane; Theo J. Moraes; Garthika Navaranjan; James A. Scott; Elinor Simons; Padmaja Subbarao; Tim K. Takaro; et al. (Environmental Research, 2024)

Atmospheric humidity regulates same-sex mating in Candida albicans through the trehalose and osmotic signaling pathways - Chao Li; Li Tao; Guobo Guan; Zhangyue Guan; Austin M. Perry; Tianren Hu; Jian Bing; Ming Xu; Clarissa J. Nobile; Guanghua Huang (Science China Life Sciences, 2023)

Targeting and image acquisition of Martian surface features with TGO/CaSSIS - M. Almeida; M. Read; N. Thomas; G. Cremonese; P. Becerra; G. Borrini; S. Byrne; M. Gruber; R. Heyd; C.M. Marriner; G. McArthur; A.S. McEwen; et al. (Planetary and Space Science, 2023)

Effect of post-harvest processing methods on the microbial safety of edible seaweed - Jessica G. Vorse; Colleen T. Moody; Lyle C. Massoia; Jennifer J. Perry; Kristin M. Burkholder; Carrie J. Byron (Journal of Applied Phycology, 2023)
The American seaweed industry is growing, primarily into the edible sector, and more seaweed products are available for human consumption. It is necessary to evaluate the safety of industry’s current post-harvest storage and processing methods to ensure the risk of foodborne pathogens on edible seaweed remains low. We evaluated the pathogen load of edible kelp post-harvest under three different storage temperatures (4˚C, 10˚C, 20˚C) and two different drying methods (air- and freeze-drying). The focal pathogens for this research included: Listeria monocytogenes, Salmonella enterica, Staphylococcus aureus, pathogenic Escherichia coli, Vibrio vulnificus and Vibrio parahaemolyticus . We tested all six pathogens under each treatment condition on both sugar kelp ( Saccharina latissima) and rockweed ( Ascophyllum nodosum ) as these are the most commonly farmed and wild-harvested species in Maine, respectively. We inoculated a known concentration of pathogen onto freshly harvested kelp, treated it under a storage temperature or drying method, and sampled it over time to determine the impact of treatment on pathogen load. Our results showed that storage at 20˚C can lead to replication while storage at 4˚C and 10˚C halted the replication of focal pathogens. Both air-drying and freeze-drying produced significant log scale reductions in surface pathogen load for all focal pathogens. Additionally, air-drying reduced pathogen load more than freeze-drying for a majority of pathogens and storing dried kelp for 6-weeks further reduced pathogen load across all cases. These results are promising for industry as they corroborate historical evidence that current post-harvest storage and processing conditions are producing products safe for human consumption.

Electrocardiogram to Determine Mitral and Aortic Valve Opening and Closure - M. Rifqi Aufan; Zachary T. Jost; Neal J. Miller; Oleg F. Sharifov; Himanshu Gupta; Gilbert J. Perry; J. Michael Wells; Thomas S. Denney; Steven G. Lloyd (Cardiovascular Engineering and Technology, 2023)

Retrieving canopy nitrogen concentration and aboveground biomass with deep learning for ryegrass and barley: Comparing models and determining waveband contribution - Manish Kumar Patel; José Padarian; Andrew W. Western; Glenn J. Fitzgerald; Alex B. McBratney; Eileen M. Perry; Helen Suter; Dongryeol Ryu (Field Crops Research, 2023)

Lehigh, a Variety with Yellow Flesh and Resistance to the Golden Cyst Nematode and Common Scab - Walter S. De Jong; Donald E. Halseth; Robert L. Plaisted; Xiaohong Wang; Keith L. Perry; Xinshun Qu; Ken M. Paddock; Matthew Falise; Barbara J. Christ; Gregory A. Porter (American Journal of Potato Research, 2023)

Reprint of: COVID-19 messaging in U.S. state parks: Extensions of the outdoor recreation strategies and practices framework unmasked by the pandemic - Elizabeth E. Perry; Kimberly J. Coleman; Tatiana A. Iretskaia; Jordan M. Baer; Liesl F. Magnus; Peter R. Pettengill (Journal of Outdoor Recreation and Tourism, 2023)

Nutrient function over form: Organic and inorganic nitrogen additions have similar effects on lake phytoplankton nutrient limitation - Sabrina N. Volponi; Heather L. Wander; David C. Richardson; Clayton J. Williams; Denise A. Bruesewitz; Shelley Arnott; Jennifer A. Brentrup; Hailee L. Edwards; Holly A. Ewing; Kristen Holeck; Lauren Johnson; Brian S. Kim; et al. (Limnology and Oceanography, 2023)
The concentration of dissolved organic nitrogen (DON) is increasing in many northern hemisphere lakes, yet its use by phytoplankton and fate in the environment seldom have been quantified. We conducted 1 week, in situ, microcosm incubations across 25 lakes in northeastern North America to understand how DON, dissolved inorganic nitrogen (DIN), and dissolved inorganic phosphorus (P) affected phytoplankton biomass. In addition, we tested whether lakes were limited by single macronutrients (N or P) or colimited by both. Phytoplankton biomass in 80% of lakes responded similarly to DON and DIN additions. Of the lakes where N form produced differential responses, the majority of phytoplankton communities exhibited greater biomass accumulation with DON than DIN. Colimitation was the most common type of nutrient limitation among the study lakes, followed by P limitation. Limitation type shifted with N form in 40% of the study lakes, but without consistent patterns explaining how shifts occurred. Regardless of N form, lakes with watersheds more dominated by agriculture and higher total dissolved nitrogen (TDN) tended to show P‐limited phytoplankton responses, while lakes with less agricultural watersheds and lower TDN tended to show colimited phytoplankton responses. Finally, ambient TDN and total phosphorus (TP) nutrient concentrations were stronger predictors of limitation type than ambient TDN : TP ratios. The different contributions of DON and DIN to phytoplankton biomass in some of our study lakes suggest that DON loading from surrounding watersheds may be an overlooked component in predicting phytoplankton productivity and nutrient limitation dynamics in freshwater ecosystems.

Improving sightings-derived residency estimation for whale shark aggregations: A novel metric applied to a global data set - Gonzalo Araujo; Ariana Agustines; Steffen S. Bach; Jesse E. M. Cochran; Emilio de la Parra-Galván; Rafael de la Parra-Venegas; Stella Diamant; Alistair Dove; Steve Fox; Rachel T. Graham; Sofia M. Green; Jonathan R. Green; et al. (Frontiers in Marine Science, 2022)
The world’s largest extant fish, the whale shark Rhincodon typus , is one of the most-studied species of sharks globally. The discovery of predictable aggregation sites where these animals gather seasonally or are sighted year-round – most of which are coastal and juvenile-dominated – has allowed for a rapid expansion of research on this species. The most common method for studying whale sharks at these sites is photographic identification (photo-ID). This technique allows for long-term individual-based data to be collected which can, in turn, be used to evaluate population structure, build population models, identify long-distance movements, and assess philopatry and other population dynamics. Lagged identification rate (LIR) models have fewer underlying assumptions than more traditional capture mark recapture approaches, making them more broadly applicable to marine taxa, especially far-ranging megafauna species like whale sharks. However, the increased flexibility comes at a cost. Parameter estimations based on LIR can be difficult to interpret and may not be comparable between areas with different sampling regimes. Using a unique data-set from the Philippines with ~8 years of nearly continuous survey effort, we were able to derive a metric for converting LIR residency estimates into more intuitive days-per-year units. We applied this metric to 25 different sites allowing for the first quantitatively-meaningful comparison of sightings-derived residence among the world’s whale shark aggregations. We validated these results against the only three published acoustic residence metrics (falling within the ranges established by these earlier works in all cases). The results were then used to understand residency behaviours exhibited by the sharks at each site. The adjusted residency metric is an improvement to LIR-based population modelling, already one of the most widely used tools for describing whale shark aggregations. The standardised methods presented here can serve as a valuable tool for assessing residency patterns of whale sharks, which is crucial for tailored conservation action, and can cautiously be tested in other taxa.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Dynamics and predicted distribution of an irrupting ‘sleeper’ population: fallow deer in Tasmania - Calum X. Cunningham; George L. W. Perry; David M. J. S. Bowman; David M. Forsyth; Michael M. Driessen; Matt Appleby; Barry W. Brook; Greg Hocking; Jessie C. Buettel; Ben J. French; Rowena Hamer; Sally L. Bryant; et al. (Biological Invasions, 2022)

The Effect of Marsh Age on Ecosystem Function in a Rapidly Transgressing Marsh - Amy K. Langston; Daniel J. Coleman; Nathalie W. Jung; Justin L. Shawler; Alexander J. Smith; Bethany L. Williams; Serina S. Wittyngham; Randolph M. Chambers; James E. Perry; Matthew L. Kirwan (Ecosystems, 2022)

Recursive Bayesian computation facilitates adaptive optimal design in ecological studies - Clinton B. Leach; Perry J. Williams; Joseph M. Eisaguirre; Jamie N. Womble; Michael R. Bower; Mevin B. Hooten (Ecology, 2022)
Optimal design procedures provide a framework to leverage the learning generated by ecological models to flexibly and efficiently deploy future monitoring efforts. At the same time, Bayesian hierarchical models have become widespread in ecology and offer a rich set of tools for ecological learning and inference. However, coupling these methods with an optimal design framework can become computationally intractable. Recursive Bayesian computation offers a way to substantially reduce this computational burden, making optimal design accessible for modern Bayesian ecological models. We demonstrate the application of so‐called prior‐proposal recursive Bayes to optimal design using a simulated data binary regression and the real‐world example of monitoring and modeling sea otters in Glacier Bay, Alaska. These examples highlight the computational gains offered by recursive Bayesian methods and the tighter fusion of monitoring and science that those computational gains enable.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Wave exposure shapes reef community composition and recovery trajectories at a remote coral atoll - Ines D. Lange; Cassandra E. Benkwitt; Jamie M. McDevitt-Irwin; Kristina L. Tietjen; Brett Taylor; Mark Chinkin; Rachel L. Gunn; Melissa Palmisciano; Margaux Steyaert; Bry Wilson; Holly K. East; John Turner; et al. (Coral Reefs, 2021)
In a time of unprecedented ecological change, understanding natural biophysical relationships between reef resilience and physical drivers is of increasing importance. This study evaluates how wave forcing structures coral reef benthic community composition and recovery trajectories after the major 2015/2016 bleaching event in the remote Chagos Archipelago, Indian Ocean. Benthic cover and substrate rugosity were quantified from digital imagery at 23 fore reef sites around a small coral atoll (Salomon) in 2020 and compared to data from a similar survey in 2006 and opportunistic surveys in intermediate years. Cluster analysis and principal component analysis show strong separation of community composition between exposed (modelled wave exposure > 1000 J m −3 ) and sheltered sites (< 1000 J m −3 ) in 2020. This difference is driven by relatively high cover of Porites sp., other massive corals, encrusting corals, soft corals, rubble and dead table corals at sheltered sites versus high cover of pavement and sponges at exposed sites. Total coral cover and rugosity were also higher at sheltered sites. Adding data from previous years shows benthic community shifts from distinct exposure-driven assemblages and high live coral cover in 2006 towards bare pavement, dead Acropora tables and rubble after the 2015/2016 bleaching event. The subsequent recovery trajectories at sheltered and exposed sites are surprisingly parallel and lead communities towards their respective pre-bleaching communities. These results demonstrate that in the absence of human stressors, community patterns on fore reefs are strongly controlled by wave exposure, even during and after widespread coral loss from bleaching events.

The Mechanical Response and Tolerance of the Anteriorly-Tilted Human Pelvis Under Vertical Loading - R. S. Salzar; E. M. Spratley; K. A. Henderson; P. C. Greenhalgh; J. Z. Zhang; B. J. Perry; J. A. McMahon (Annals of Biomedical Engineering, 2021)

The scope and severity of white‐nose syndrome on hibernating bats in North America - Tina L. Cheng; Jonathan D. Reichard; Jeremy T. H. Coleman; Theodore J. Weller; Wayne E. Thogmartin; Brian E. Reichert; Alyssa B. Bennett; Hugh G. Broders; Joshua Campbell; Katherine Etchison; Daniel J. Feller; Richard Geboy; et al. (Conservation Biology, 2021)
Assessing the scope and severity of threats is necessary for evaluating impacts on populations to inform conservation planning. Quantitative threat assessment often requires monitoring programs that provide reliable data over relevant spatial and temporal scales, yet such programs can be difficult to justify until there is an apparent stressor. Leveraging efforts of wildlife management agencies to record winter counts of hibernating bats, we collated data for 5 species from over 200 sites across 27 U.S. states and 2 Canadian provinces from 1995 to 2018 to determine the impact of white‐nose syndrome (WNS), a deadly disease of hibernating bats. We estimated declines of winter counts of bat colonies at sites where the invasive fungus that causes WNS ( Pseudogymnoascus destructans ) had been detected to assess the threat impact of WNS. Three species undergoing species status assessment by the U.S. Fish and Wildlife Service ( Myotis septentrionalis , Myotis lucifugus , and Perimyotis subflavus ) declined by more than 90%, which warrants classifying the severity of the WNS threat as extreme based on criteria used by NatureServe. The scope of the WNS threat as defined by NatureServe criteria was large (36% of Myotis lucifugus range) to pervasive (79% of Myotis septentrionalis range) for these species. Declines for 2 other species ( Myotis sodalis and Eptesicus fuscus ) were less severe but still qualified as moderate to serious based on NatureServe criteria. Data‐sharing across jurisdictions provided a comprehensive evaluation of scope and severity of the threat of WNS and indicated regional differences that can inform response efforts at international, national, and state or provincial jurisdictions. We assessed the threat impact of an emerging infectious disease by uniting monitoring efforts across jurisdictional boundaries and demonstrated the importance of coordinated monitoring programs, such as the North American Bat Monitoring Program (NABat), for data‐driven conservation assessments and planning.

Corrigendum: OceanGliders: A Component of the Integrated GOOS - Pierre Testor; Brad de Young; Daniel L. Rudnick; Scott Glenn; Daniel Hayes; Craig M. Lee; Charitha Pattiaratchi; Katherine Hill; Emma Heslop; Victor Turpin; Pekka Alenius; Carlos Barrera; et al. (Frontiers in Marine Science, 2021)

Responses of ichthyoplankton assemblages to the recent marine heatwave and previous climate fluctuations in several Northeast Pacific marine ecosystems - Jens M. Nielsen; Lauren A. Rogers; Richard D. Brodeur; Andrew R. Thompson; Toby D. Auth; Alison L. Deary; Janet T. Duffy‐Anderson; Moira Galbraith; J. Anthony Koslow; R. Ian Perry (Global Change Biology, 2021)
The effects of climate warming on ecosystem dynamics are widespread throughout the world's oceans. In the Northeast Pacific, large‐scale climate patterns such as the El Niño/Southern Oscillation and Pacific Decadal Oscillation, and recently unprecedented warm ocean conditions from 2014 to 2016, referred to as a marine heatwave (MHW), resulted in large‐scale ecosystem changes. Larval fishes quickly respond to environmental variability and are sensitive indicators of ecosystem change. Categorizing ichthyoplankton dynamics across marine ecosystem in the Northeast Pacific can help elucidate the magnitude of assemblage shifts, and whether responses are synchronous or alternatively governed by local responses to regional oceanographic conditions. We analyzed time‐series data of ichthyoplankton abundances from four ecoregions in the Northeast Pacific ranging from subarctic to subtropical: the Gulf of Alaska (1981–2017), British Columbia (2001–2017), Oregon (1998–2017), and the southern California Current (1981–2017). We assessed the impact of the recent (2014–2016) MHW and how ichthyoplankton assemblages responded to past major climate perturbations since 1981 in these ecosystems. Our results indicate that the MHW caused widespread changes in the ichthyoplankton fauna along the coast of the Northeast Pacific Ocean, but impacts differed between marine ecosystems. For example, abundances for most dominant taxa were at all‐time lows since the beginning of sampling in the Gulf of Alaska and British Columbia, while in Oregon and the southern California Current species richness increased as did abundances of species associated with warmer waters. Lastly, species associated with cold waters also increased in abundances close to shore in southern California during the MHW, a pattern that was distinctly different from previous El Niño events. We also found several large‐scale, synchronized ichthyoplankton assemblage composition shifts during past major climate events. Current climate projections suggest that MHWs will become more intense and thus our findings can help project future changes in larval dynamics, allowing for improved ecosystem management decisions.

Waneta, a Variety with Excellent Chip Color out of Cold Storage, Long Tuber Dormancy, and Resistance to the Golden Cyst Nematode - Walter S. De Jong; Donald E. Halseth; Robert L. Plaisted; Xiaohong Wang; Keith L. Perry; Xinshun Qu; Ken M. Paddock; Matthew Falise; Barbara J. Christ; Gregory A. Porter (American Journal of Potato Research, 2020)

St. Helena: An Important Reproductive Habitat for Whale Sharks (Rhincodon typus) in the Central South Atlantic - Cameron T. Perry; Elizabeth Clingham; D. Harry Webb; Rafael de la Parra; Simon J. Pierce; Annalea Beard; LeeAnn Henry; Beth Taylor; Kenickie Andrews; Rhys Hobbs; Gonzalo Araujo; Alistair D. M. Dove (Frontiers in Marine Science, 2020)

A review of a decade of lessons from one of the world’s largest MPAs: conservation gains and key challenges - Graeme C. Hays; Heather J. Koldewey; Samantha Andrzejaczek; Martin J. Attrill; Shanta Barley; Daniel T. I. Bayley; Cassandra E. Benkwitt; Barbara Block; Robert J. Schallert; Aaron B. Carlisle; Pete Carr; Taylor K. Chapple; et al. (Marine Biology, 2020)

Limited genetic parallelism underlies recent, repeated incipient speciation in geographically proximate populations of an Arctic fish ( Salvelinus alpinus ) - Sarah J. Salisbury; Gregory R. McCracken; Robert Perry; Donald Keefe; Kara K.S. Layton; Tony Kess; Cameron M. Nugent; Jong S. Leong; Ian R. Bradbury; Ben F. Koop; Moira M. Ferguson; Daniel E. Ruzzante (Molecular Ecology, 2020)
The genetic underpinnings of incipient speciation, including the genomic mechanisms which contribute to morphological and ecological differentiation and reproductive isolation, remain poorly understood. The repeated evolution of consistently, phenotypically distinct morphs of Arctic Charr ( Salvelinus alpinus ) within the Quaternary period offer an ideal model to study the repeatability of evolution at the genomic level. Sympatric morphs of Arctic Charr are found across this species' circumpolar distribution. However, the specific genetic mechanisms driving this morph differentiation are largely unknown despite the cultural and economic importance of the anadromous morph. We used a newly designed 87k SNP chip to investigate the character and consistency of the genomic differences among sympatric morphs within three recently deglaciated and geographically proximate lakes in Labrador, Canada. We found genetically distinct small and large morph Arctic Charr in all three lakes consistent with resident and anadromous morphs, respectively. A degree of reproductive isolation among sympatric morphs is likely given genome‐wide distributions of outlier SNPs and high genome‐wide F ST s. Across all lakes, outlier SNPs were largely nonoverlapping suggesting a lack of genetic parallelism driving morph differentiation. Alternatively, several genes and paralogous copies of the same gene consistently differentiated morphs across multiple lakes suggesting their importance to the manifestation of morphs. Our results confirm the utility of Arctic Charr as a model for investigating the predictability of evolution and support the importance of both genetic parallelism and nonparallelism to the incipient speciation of Arctic Charr morphs.

Correction to: “Relationships Between Salinity and Short-Term Soil Carbon Accumulation Rates from Marsh Types Across a Landscape in the Mississippi River Delta” - Melissa M. Baustian; Camille L. Stagg; Carey L. Perry; Leland C. Moss; Tim J. B. Carruthers; Mead Allison (Wetlands, 2020)

Coral Reefs of Abu Dhabi, United Arab Emirates: Analysis of Management Approaches in Light of International Best Practices and a Changing Climate - Haïfa Ben-Romdhane; Rima W. Jabado; Edwin Mark Grandcourt; Richard John Obrien Perry; Ayesha Yousef Al Blooshi; Prashanth Reddy Marpu; Taha B. M. J. Ouarda; Hosni Ghedira (Frontiers in Marine Science, 2020)

Early-earth nonprotein amino acid metabolites in modern cyanobacterial microbialites - Stephanie L. Bishop; Fiona J. M. Tymm; Karen Perry; Jeff K. Kerkovius; Frederic Menard; Allyson Brady; Greg Slater; Darlene S. S. Lim; James S. Metcalf; Sandra A. Banack; Paul A. Cox; Susan J. Murch (Environmental Chemistry Letters, 2020)

Projected late 21st century changes to the regional impacts of the El Niño-Southern Oscillation - S. J. Perry; S. McGregor; A. Sen Gupta; M. H. England; N. Maher (Climate Dynamics, 2020)

OceanGliders: A Component of the Integrated GOOS - Pierre Testor; Brad de Young; Daniel L. Rudnick; Scott Glenn; Daniel Hayes; Craig M. Lee; Charitha Pattiaratchi; Katherine Hill; Emma Heslop; Victor Turpin; Pekka Alenius; Carlos Barrera; et al. (Frontiers in Marine Science, 2019)
The OceanGliders program started in 2016 to support active coordination and enhancement of global glider activity. OceanGliders contributes to the international efforts of the Global Ocean Observation System (GOOS) for Climate, Ocean Health, and Operational Services. It brings together marine scientists and engineers operating gliders around the world: (1) to observe the long-term physical, biogeochemical, and biological ocean processes and phenomena that are relevant for societal applications; and, (2) to contribute to the GOOS through real-time and delayed mode data dissemination. The OceanGliders program is distributed across national and regional observing systems and significantly contributes to integrated, multi-scale and multi-platform sampling strategies. OceanGliders shares best practices, requirements, and scientific knowledge needed for glider operations, data collection and analysis. It also monitors global glider activity and supports the dissemination of glider data through regional and global databases, in real-time and delayed modes, facilitating data access to the wider community. OceanGliders currently supports national, regional and global initiatives to maintain and expand the capabilities and application of gliders to meet key global challenges such as improved measurement of ocean boundary currents, water transformation and storm forecast.

Proximal fluorescence sensing of potassium responsive crops to develop improved predictions of biomass, yield and grain quality of wheat and barley - Jonathan Eddison Holland; Davide Cammarano; Glenn J. Fitzgerald; Eileen M. Perry; Graeme Poile; Mark Kenneth Conyers (Precision Agriculture, 2019)

The Second Warning to Humanity – Providing a Context for Wetland Management and Policy - C. M. Finlayson; Gillian T. Davies; William R. Moomaw; G. L. Chmura; Susan M. Natali; J. E. Perry; N. Roulet; Ariana E. Sutton-Grier (Wetlands, 2019)

Evaluation of a traditional Māori harvesting method for sampling kōura (freshwater crayfish, Paranephrops planifrons ) and toi toi (bully, Gobiomorphus spp.) populations in two New Zealand streams - Ian A. Kusabs; Brendan J. Hicks; John M. Quinn; William L. Perry; Hēmi Whaanga (New Zealand Journal of Marine and Freshwater Research, 2018)
Representative sampling of crayfish in streams is often impractical, especially in non‐wadable habitats, or in areas with soft substrates. Whakaweku are artificial habitats made from bracken fern ( Pteridium esculentum ) that can be used successfully in a range of habitats. We compared whakaweku, minnow traps, fyke nets and electrofishing for sampling freshwater crayfish (kōura; Paranephrops planifrons ) and bullies (toi toi; Gobiomorphus spp .) in two streams with differing stream characteristics and fish assemblages. Whakaweku captured a full‐size range of kōura of both sexes, including small kōura (OCL 7–12 mm) that were not caught by minnow traps or fyke nets. Colonisation by kōura reached 90% of maximum after 2 weeks and CPUE was constant from 2 to 9 weeks. After 9 weeks, CPUE decreased due to decay of the fern fronds. Whakaweku are an effective sampling tool that are inexpensive, simple to set, and do not require expensive equipment or specialised training.

Novel ecological and climatic conditions drive rapid adaptation in invasive Florida Burmese pythons - Daren C. Card; Blair W. Perry; Richard H. Adams; Drew R. Schield; Acacia S. Young; Audra L. Andrew; Tereza Jezkova; Giulia I.M. Pasquesi; Nicole R. Hales; Matthew R. Walsh; Michael R. Rochford; Frank J. Mazzotti; et al. (Molecular Ecology, 2018)
Invasive species provide powerful in situ experimental systems for studying evolution in response to selective pressures in novel habitats. While research has shown that phenotypic evolution can occur rapidly in nature, few examples exist of genomewide adaptation on short “ecological” timescales. Burmese pythons ( Python molurus bivittatus ) have become a successful and impactful invasive species in Florida over the last 30 years despite major freeze events that caused high python mortality. We sampled Florida Burmese pythons before and after a major freeze event in 2010 and found evidence for directional selection in genomic regions enriched for genes associated with thermosensation, behaviour and physiology. Several of these genes are linked to regenerative organ growth, an adaptive response that modulates organ size and function with feeding and fasting in pythons. Independent histological and functional genomic data sets provide additional layers of support for a contemporary shift in invasive Burmese python physiology. In the Florida population, a shift towards maintaining an active digestive system may be driven by the fitness benefits of maintaining higher metabolic rates and body temperature during freeze events. Our results suggest that a synergistic interaction between ecological and climatic selection pressures has driven adaptation in Florida Burmese pythons, demonstrating the often‐overlooked potential of rapid adaptation to influence the success of invasive species.

A multidisciplinary-based conceptual model of a fractured sedimentary bedrock aquitard: improved prediction of aquitard integrity - Anthony C. Runkel; Robert G. Tipping; Jessica R. Meyer; Julia R. Steenberg; Andrew J. Retzler; Beth L. Parker; Jeff A. Green; John D. Barry; Perry M. Jones (Hydrogeology Journal, 2018)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Wetlands In a Changing Climate: Science, Policy and Management - William R. Moomaw; G. L. Chmura; Gillian T. Davies; C. M. Finlayson; B. A. Middleton; Susan M. Natali; J. E. Perry; N. Roulet; Ariana E. Sutton-Grier (Wetlands, 2018)

Does heating stimulate germination in Leptospermum scoparium (mānuka; Myrtaceae)? - Paul F. Battersby; Janet M. Wilmshurst; Timothy J. Curran; George L. W. Perry (New Zealand Journal of Botany, 2017)
Fire regimes are powerful selective filters. In New Zealand, fire activity was rare before human settlement, and New Zealand’s indigenous woody flora shows little adaptation to frequent fire. One of the few woody indigenous species to show adaptation to frequent fire is Leptospermum scoparium (Myrtaceae), a Plio‐Pleistocene immigrant from Australia. Leptospermum scoparium is a widespread early‐successional shrub to small tree that frequently dominates post‐fire successions, and shows geographically‐variable pyriscent serotiny, a fire‐adaptation in which seeds are retained in the canopy and open post‐fire. Another widespread reproductive adaptation to fire is heat‐stimulated germination. Some Australian Leptospermum respond positively to heat treatment, and observations in New Zealand suggest that the seeds of L. scoparium within thick‐walled capsules open immediately after fire and successfully germinate, indicating at least no deleterious effect of heating. In some fire‐prone systems such as Mediterranean shrublands, traits such as serotiny and heat‐stimulated germination have been positively associated with traits associated with flammability (e.g. retention of dead fuel). Here we evaluate the effect of heat stimulation (short exposure to high temperatures) of capsules on germination in L. scoparium from New Zealand, and evaluate links between germination, serotiny and shoot‐level flammability. Germination trials using seed collected from 12 populations indicated no consistent positive or negative effect of heat treatment on germination success (germinability). These trials suggest that the capsules of L. scoparium at least provide adequate insulation to heating. Germinability was not consistently related to either serotiny or flammability; nor was it related to latitude or elevation. While taxa from other fire‐prone ecosystems may show coordinated trait responses to fire, the lack of association between physical measures of flammability and germination rates indicate that this is not the case in L. scoparium , New Zealand’s most fire‐adapted indigenous woody species.

Soil or fire: what causes treeless sedgelands in Tasmanian wet forests? - David M. J. S. Bowman; George L. W. Perry (Plant and Soil, 2017)

Palaeoecological records of coral community development on a turbid, nearshore reef complex: baselines for assessing ecological change - J. A. Johnson; C. T. Perry; S. G. Smithers; K. M. Morgan; N. Santodomingo; K. G. Johnson (Coral Reefs, 2017)

Methyl isonicotinate — a non-pheromone thrips semiochemical — and its potential for pest management - D. A. J. Teulon; M. M. Davidson; N. B. Perry; M. -C. Nielsen; C. Castañé; D. Bosch; J. Riudavets; R. W. H. M. van Tol; W. J. de Kogel (International Journal of Tropical Insect Science, 2017)

Exploring fire adaptation in a land with little fire: serotiny in Leptospermum scoparium (Myrtaceae) - Paul F. Battersby; Janet M. Wilmshurst; Timothy J. Curran; Matthew S. McGlone; George L. W. Perry (Journal of Biogeography, 2017)
Aim Immigrant floras often have distinctive traits, well suited to the host region but absent from the autochthonous flora. An example is serotiny in the New Zealand ( NZ ) small tree, Leptospermum scoparium (Myrtaceae) belonging to a strongly fire‐adapted Australian clade. Serotiny in L. scoparium has been attributed either to strong selection by fire since human settlement, or taken as evidence that pre‐human fire in NZ was more important than assumed. By integrating field data, experimental analyses and long‐term fire histories, we sought to explain the spatial pattern of serotiny in L. scoparium in NZ , and evaluate these two explanations. Location New Zealand. Methods We quantified the distribution of serotiny in L. scoparium by analysing 137 populations distributed across NZ (two previous studies and ours), including 31 with Holocene fire histories. We assessed the relationship of serotiny with a suite of fire and climate environmental predictors, and between serotiny and shoot‐level flammability. Results Serotiny was strongly positively associated with latitude (more in the north), lower rainfall and higher temperatures. Serotinous populations were rare at sites with no history of fire. Serotiny was most prevalent in northern wetlands, where fire was recurrent during the Holocene, but was nearly absent from the southwestern Southern Alps. Shoot‐level flammability and serotiny were not correlated. Main conclusions The distribution of serotiny in L. scoparium relates not only to current environments but also to the legacy of regional shifts in vegetation during Quaternary glacial–interglacial cycles. Serotiny was maintained where the landscape experienced sporadic fire, but it is absent from NZ 's southern South Island because the sparse, open vegetation during the glacials did not support fire. Serotinous L. scoparium populations were therefore more common in the northern North Island. Human transformation of the fire regime over the last 750 years has likely favoured the spread of serotinous populations.

Warming and provenance limit tree recruitment across and beyond the elevation range of subalpine forest - Lara M. Kueppers; Erin Conlisk; Cristina Castanha; Andrew B. Moyes; Matthew J. Germino; Perry de Valpine; Margaret S. Torn; Jeffry B. Mitton (Global Change Biology, 2017)
Climate niche models project that subalpine forest ranges will extend upslope with climate warming. These projections assume that the climate suitable for adult trees will be adequate for forest regeneration, ignoring climate requirements for seedling recruitment, a potential demographic bottleneck. Moreover, local genetic adaptation is expected to facilitate range expansion, with tree populations at the upper forest edge providing the seed best adapted to the alpine. Here, we test these expectations using a novel combination of common gardens, seeded with two widely distributed subalpine conifers, and climate manipulations replicated at three elevations. Infrared heaters raised temperatures in heated plots, but raised temperatures more in the forest than at or above treeline because strong winds at high elevation reduced heating efficiency. Watering increased season‐average soil moisture similarly across sites. Contrary to expectations, warming reduced Engelmann spruce recruitment at and above treeline, as well as in the forest. Warming reduced limber pine first‐year recruitment in the forest, but had no net effect on fourth‐year recruitment at any site. Watering during the snow‐free season alleviated some negative effects of warming, indicating that warming exacerbated water limitations. Contrary to expectations of local adaptation, low‐elevation seeds of both species initially recruited more strongly than high‐elevation seeds across the elevation gradient, although the low‐provenance advantage diminished by the fourth year for Engelmann spruce, likely due to small sample sizes. High‐ and low‐elevation provenances responded similarly to warming across sites for Engelmann spruce, but differently for limber pine. In the context of increasing tree mortality, lower recruitment at all elevations with warming, combined with lower quality, high‐provenance seed being most available for colonizing the alpine, portends range contraction for Engelmann spruce. The lower sensitivity of limber pine to warming indicates a potential for this species to become more important in subalpine forest communities in the coming centuries.

Relationships Between Salinity and Short-Term Soil Carbon Accumulation Rates from Marsh Types Across a Landscape in the Mississippi River Delta - Melissa M. Baustian; Camille L. Stagg; Carey L. Perry; Leland C. Moss; Tim J. B. Carruthers; Mead Allison (Wetlands, 2017)

Lamoka, a Variety with Excellent Chip Color Out of Cold Storage and Resistance to the Golden Cyst Nematode - Walter S. De Jong; Donald E. Halseth; Robert L. Plaisted; Xiaohong Wang; Keith L. Perry; Xinshun Qu; Ken M. Paddock; Matthew Falise; Barbara J. Christ; Gregory A. Porter (American Journal of Potato Research, 2017)

Commentary: On the water footprint as an indicator of water use in food production - E. Fereres; F. J. Villalobos; F. Orgaz; M. I. Minguez; G. van Halsema; C. J. Perry (Irrigation Science, 2017)

The basis function approach for modeling autocorrelation in ecological data - Trevor J. Hefley; Kristin M. Broms; Brian M. Brost; Frances E. Buderman; Shannon L. Kay; Henry R. Scharf; John R. Tipton; Perry J. Williams; Mevin B. Hooten (Ecology, 2017)
Analyzing ecological data often requires modeling the autocorrelation created by spatial and temporal processes. Many seemingly disparate statistical methods used to account for autocorrelation can be expressed as regression models that include basis functions. Basis functions also enable ecologists to modify a wide range of existing ecological models in order to account for autocorrelation, which can improve inference and predictive accuracy. Furthermore, understanding the properties of basis functions is essential for evaluating the fit of spatial or time‐series models, detecting a hidden form of collinearity, and analyzing large data sets. We present important concepts and properties related to basis functions and illustrate several tools and techniques ecologists can use when modeling autocorrelation in ecological data.

Salbutamol effects on systemic potassium dynamics during and following intense continuous and intermittent exercise - Muath M. Altarawneh; Aaron Petersen; Robert Smith; David M. Rouffet; Francois Billaut; Ben D. Perry; Victoria L. Wyckelsma; Antony Tobin; Michael J. McKenna (European Journal of Applied Physiology, 2016)

Review of Fusarium species isolated in association with mango malformation in Australia - E. C. Y. Liew; M. H. Laurence; C. A. Pearce; R. G. Shivas; G. I. Johnson; Y.P. Tan; J. Edwards; S. Perry; A.W. Cooke; B. A. Summerell (Australasian Plant Pathology, 2016)

Long-Term Trends of Nutrients and Phytoplankton in Chesapeake Bay - L. W. Harding; C. L. Gallegos; E. S. Perry; W. D. Miller; J. E. Adolf; M. E. Mallonee; H. W. Paerl (Estuaries and Coasts, 2016)

An Overview of Occupational Risks From Climate Change - Katie M. Applebaum; Jay Graham; George M. Gray; Peter LaPuma; Sabrina A. McCormick; Amanda Northcross; Melissa J. Perry (Current Environmental Health Reports, 2016)

Exotic Mammals and Invasive Plants Alter Fire-Related Thresholds in Southern Temperate Forested Landscapes - George L. W. Perry; Janet M. Wilmshurst; John Ogden; Neal J. Enright (Ecosystems, 2015)

A systematic review of dietary, nutritional, and physical activity interventions for the prevention of prostate cancer progression and mortality - Lucy E. Hackshaw-McGeagh; Rachel E. Perry; Verity A. Leach; Sara Qandil; Mona Jeffreys; Richard M. Martin; J. Athene Lane (Cancer Causes & Control, 2015)

The Y ersinia pestis HmsCDE regulatory system is essential for blockage of the oriental rat flea ( X enopsylla cheopis ), a classic plague vector - Alexander G. Bobrov; Olga Kirillina; Viveka Vadyvaloo; Benjamin J. Koestler; Angela K. Hinz; Dietrich Mack; Christopher M. Waters; Robert D. Perry (Environmental Microbiology, 2015)
Summary The second messenger molecule cyclic diguanylate is essential for Y ersinia pestis biofilm formation that is important for blockage‐dependent plague transmission from fleas to mammals. Two diguanylate cyclases ( DGCs ) HmsT and Y 3730 ( HmsD ) are responsible for biofilm formation in vitro and biofilm‐dependent blockage in the oriental rat flea X enopsylla cheopis respectively. Here, we have identified a tripartite signalling system encoded by the y3729‐y3731 operon that is responsible for regulation of biofilm formation in different environments. We present genetic evidence that a putative inner membrane‐anchored protein with a large periplasmic domain Y 3729 ( HmsC ) inhibits HmsD DGC activity in vitro while an outer membrane P al‐like putative lipoprotein Y 3731 ( HmsE ) counteracts HmsC to activate HmsD in the gut of X . cheopis . We propose that HmsE is a critical element in the transduction of environmental signal(s) required for HmsD ‐dependent biofilm formation.

Evaluation of a new chromogenic medium, chromID OXA-48, for recovery of carbapenemase-producing Enterobacteriaceae from patients at a university hospital in Turkey - P. Zarakolu; K. M. Day; H. E. Sidjabat; W. Kamolvit; C. V. Lanyon; S. P. Cummings; D. L. Paterson; M. Akova; J. D. Perry (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

Capsaicin induces apoptosis in human small cell lung cancer via the TRPV6 receptor and the calpain pathway - Jamie K. Lau; Kathleen C. Brown; Aaron M. Dom; Theodore R. Witte; Brent A. Thornhill; Clayton M. Crabtree; Haley E. Perry; J. Michael Brown; John G. Ball; Rebecca G. Creel; C. Luke Damron; William D. Rollyson; et al. (Apoptosis, 2014)

Relationships between aerosols and precipitation in the southern Appalachian Mountains - G. M. Kelly; B. F. Taubman; L. B. Perry; J. P. Sherman; P. T. Soulé; P. J. Sheridan (International Journal of Climatology, 2013)
There are many uncertainties associated with aerosol‐precipitation interactions, particularly in mountain regions where a variety of processes at different spatial scales influence precipitation patterns. Statistical relationships between aerosols and precipitation were examined in the southern Appalachian Mountains to determine the seasonal and synoptic influences on these relationships, as well as the influence of air mass source region. Precipitation events were identified based on regional precipitation data and classified using a synoptic classification scheme developed for this study and published in a separate manuscript (Kelly et al . 2012). Hourly aerosol data were collected at the Appalachian Atmospheric Interdisciplinary Research ( AppalAIR ) facility at Appalachian State University in Boone, NC (1110 m asl, 36.215°, –81.680°). Backward air trajectories provided information on upstream atmospheric characteristics and source regions. During the warm season (June–September), greater aerosol loading dominated by larger particles was observed, whereas cool season (November–April) precipitation events exhibited overall lower aerosol loading with an apparent influence from biomass burning particles. A significant relationship between aerosol optical properties and precipitation intensity was observed, which may be indicative of aerosol‐induced precipitation enhancement in each season, particularly during warm season non‐frontal precipitation.

Improvements to Rapfish: a rapid evaluation technique for fisheries integrating ecological and human dimensions a - T. J. Pitcher; M. E. Lam; C. Ainsworth; A. Martindale; K. Nakamura; R. I. Perry; T. Ward (Journal of Fish Biology, 2013)
This paper reports recent developments in Rapfish, a normative, scalable and flexible rapid appraisal technique that integrates both ecological and human dimensions to evaluate the status of fisheries in reference to a norm or goal. Appraisal status targets may be sustainability, compliance with a standard (such as the UN code of conduct for responsible fisheries) or the degree of progress in meeting some other goal or target. The method combines semi‐quantitative ( e.g . ecological) and qualitative ( e.g . social) data via multiple evaluation fields, each of which is assessed through scores assigned to six to 12 attributes or indicators: the scoring method allows user flexibility to adopt a wide range of utility relationships. For assessing sustainability, six evaluation fields have been developed: ecological, technological, economic, social, ethical and institutional. Each field can be assessed directly with a set of scored attributes, or several of the fields can be dealt with in greater detail using nested subfields that themselves comprise multidimensional Rapfish assessments ( e.g . the hierarchical institutional field encompasses both governance and management, including a detailed analysis of legality). The user has the choice of including all or only some of the available sustainability fields. For the attributes themselves, there will rarely be quantitative data, but scoring allows these items to be estimated. Indeed, within a normative framework, one important advantage with Rapfish is transparency of the rigour, quality and replicability of the scores. The Rapfish technique employs a constrained multidimensional ordination that is scaled to situate data points within evaluation space. Within each evaluation field, results may be presented as a two‐dimensional plot or in a one‐dimensional rank order. Uncertainty is expressed through the probability distribution of Monte‐Carlo simulations that use the c.l . on each original observation. Overall results of the multidisciplinary analysis may be shown using kite diagrams that compare different locations, time periods (including future projections) and management scenarios, which make policy trade‐offs explicit. These enhancements are now available in the R programming language and on an open website, where users can run Rapfish analyses by downloading the software or uploading their data to a user interface.

A conceptual framework for predicting temperate ecosystem sensitivity to human impacts on fire regimes - D. B. McWethy; P. E. Higuera; C. Whitlock; T. T. Veblen; D. M. J. S. Bowman; G. J. Cary; S. G. Haberle; R. E. Keane; B. D. Maxwell; M. S. McGlone; G. L. W. Perry; J. M. Wilmshurst; et al. (Global Ecology and Biogeography, 2013)
Aim The increased incidence of large fires around much of the world in recent decades raises questions about human and non‐human drivers of fire and the likelihood of increased fire activity in the future. The purpose of this paper is to outline a conceptual framework for examining where human‐set fires and feedbacks are likely to be most pronounced in temperate forests world‐wide and to establish and test a methodology for evaluating this framework using palaeoecological records. Location T asmania, north‐western USA , southern S outh A merica and N ew Z ealand. Methods We outline a conceptual framework for predicting the sensitivity of ecosystems to human impacts on fire regimes and then use a circum‐ P acific comparison of existing historical reconstructions of fire, climate, human settlement and vegetation to evaluate this approach. Results Previous research investigating important controls on fire activity shows that the sensitivity of temperate ecosystems to human‐set fires is modulated by the frequency of natural fire occurrence, fuel moisture and fuel type and availability. Palaeoecological data from four temperate regions suggest that the effects of anthropogenic burning are greatest where fire is naturally rare, vegetation is poorly adapted to fire and fuel biomass is abundant and contiguous. Alternatively, where fire activity is naturally high and vegetation is well adapted to fire, evidence of human influence on fire and vegetation is less obvious. Main conclusions Palaeofire records suggest that the most dynamic and persistent ecosystem transitions occur where human activities increase landscape flammability through fire–vegetation feedbacks. Rapid forest transitions in biomass‐rich ecosystems such as N ew Z ealand and areas of Tasmania and southern South America illustrate how landscapes experiencing few fires can shift past tipping points to become fire‐prone landscapes with new alternative stable state communities. Comparisons of palaeoecological data from different regions with similar biophysical gradients but different human settlement histories can provide new opportunities for understanding ecosystem vulnerability to fire–climate–human interactions.

Effects of risperidone, amisulpride and nicotine on eye movement control and their modulation by schizotypy - Anne Schmechtig; Jane Lees; Lois Grayson; Kevin J. Craig; Rukiya Dadhiwala; Gerard R. Dawson; J. F. William Deakin; Colin T. Dourish; Ivan Koychev; Katrina McMullen; Ellen M. Migo; Charlotte Perry; et al. (Psychopharmacology, 2013)

Human temperature regulation when given the opportunity to behave - Zachary J. Schlader; Blake G. Perry; M. Rahimi Che Jusoh; Lynette D. Hodges; Stephen R. Stannard; Toby Mündel (European Journal of Applied Physiology, 2013)

The spatial distribution of canopy-resident and ground-resident cereal aphids (Sitobion avenae and Metopolophium dirhodum) in winter wheat - Linton Winder; Colin J. Alexander; Chris Woolley; Joe N. Perry; John M. Holland (Arthropod-Plant Interactions, 2013)

Amplified fragment length polymorphism-based genetic diversity among cultivated and weedy rye (Secale cereale L.) accessions - T. Chikmawati; M. Miftahudin; B. Skovmand; J. Perry Gustafson (Genetic Resources and Crop Evolution, 2012)

Dodo remains from an in situ context from Mare aux Songes, Mauritius - Hanneke J. M. Meijer; Arike Gill; Perry G. B. de Louw; Lars W. Van Den Hoek Ostende; Julian P. Hume; Kenneth F. Rijsdijk (The Science of Nature, 2012)

Compensatory regulation of acid–base balance during salinity transfer in rainbow trout (Oncorhynchus mykiss) - K. M. Gilmour; S. F. Perry; A. J. Esbaugh; J. Genz; J. R. Taylor; M. Grosell (Journal of Comparative Physiology B, 2012)

Drivers of region-wide declines in architectural complexity on Caribbean reefs - Lorenzo Alvarez-Filip; J. A. Gill; N. K. Dulvy; A. L. Perry; A. R. Watkinson; I. M. Côté (Coral Reefs, 2011)

Optimal plant densities of lucerne (Medicago sativa) for pasture production and soil water extraction in mixed pastures in south-western Australia - Perry J. Dolling; Anita M. Lyons; Roy A. Latta (Plant and Soil, 2011)

FUS Immunogold Labeling TEM Analysis of the Neuronal Cytoplasmic Inclusions of Neuronal Intermediate Filament Inclusion Disease: A Frontotemporal Lobar Degeneration with FUS Proteinopathy - Tristan Page; Michael A. Gitcho; Sabrina Mosaheb; Deborah Carter; Sumi Chakraverty; Robert H. Perry; Eileen H. Bigio; Marla Gearing; Isidre Ferrer; Alison M. Goate; Nigel J. Cairns; Julian R. Thorpe (Journal of Molecular Neuroscience, 2011)

Mercury in breeding saltmarsh sparrows (Ammodramus caudacutus caudacutus) - Oksana P. Lane; Kathleen M. O’Brien; David C. Evers; Thomas P. Hodgman; Andrew Major; Nancy Pau; Mark J. Ducey; Robert Taylor; Deborah Perry (Ecotoxicology, 2011)

Roles of cortisol and carbonic anhydrase in acid–base compensation in rainbow trout, Oncorhynchus mykiss - K. M. Gilmour; C. L. Collier; C. J. Dey; S. F. Perry (Journal of Comparative Physiology B, 2010)

Erratum to: Measuring sediment accretion in early tidal marsh restoration - John Y. Takekawa; Isa Woo; Nicole D. Athearn; Scott Demers; Rachel J. Gardiner; William M. Perry; Neil K. Ganju; Gregory G. Shellenbarger; David H. Schoellhamer (Wetlands Ecology and Management, 2010)

Remote Sensing and Economic Indicators for Supporting Water Resources Management Decisions - Petra J. G. J. Hellegers; Richard Soppe; Chris J. Perry; Wim G. M. Bastiaanssen (Water Resources Management, 2010)

Measuring sediment accretion in early tidal marsh restoration - John Y. Takekawa; Isa Woo; Nicole D. Athearn; Scott Demers; Rachel J. Gardiner; William M. Perry; Neil K. Ganju; Gregory G. Shellenbarger; David H. Schoellhamer (Wetlands Ecology and Management, 2010)

Spatial variation in tree characteristics and yield in a pear orchard - Eileen M. Perry; Raymond J. Dezzani; Clark F. Seavert; Francis J. Pierce (Precision Agriculture, 2010)

Clinical and molecular epidemiology of ciprofloxacin-susceptible MRSA encoding PVL in England and Wales - M. J. Ellington; C. Perry; M. Ganner; M. Warner; I. McCormick Smith; R. L. Hill; L. Shallcross; S. Sabersheikh; A. Holmes; B. D. Cookson; A. M. Kearns (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

The fire frequency analysis branch of the pyrostatistics tree: sampling decisions and censoring in fire interval data - Max A. Moritz; Tadashi J. Moody; Lori J. Miles; Matthew M. Smith; Perry de Valpine (Environmental and Ecological Statistics, 2009)

A therapeutic dose of zolpidem reduces thalamic GABA in healthy volunteers: a proton MRS study at 4 T - Stephanie C. Licata; J. Eric Jensen; David M. Penetar; Andrew P. Prescot; Scott E. Lukas; Perry F. Renshaw (Psychopharmacology, 2009)

Combining remote sensing and economic analysis to support decisions that affect water productivity - P. J. G. J. Hellegers; R. Soppe; C. J. Perry; W. G. M. Bastiaanssen (Irrigation Science, 2009)

DNA-Protein Cross-Links in Erythrocytes of Freshwater Fish Exposed to Hexavalent Chromium or Divalent Nickel - Jim R. Kuykendall; Kyle L. Miller; Kristen M. Mellinger; Andrew J. Cain; Michael W. Perry; Michael Bradley; Eric J. Jarvi; Dennis J. Paustenbach (Archives of Environmental Contamination and Toxicology, 2009)

Seaglider observations of blooms and subsurface chlorophyll maxima off the Washington coast - M. J. Perry; B. S. Sackmann; C. C. Eriksen; C. M. Lee (Limnology and Oceanography, 2008)
From September 2003 to December 2007, autonomous, underwater Seaglider continuously ran a V‐shaped transect off Washington State from about 200‐m water depth (i.e., at the break between the shelf and slope) to offshore waters with depths >2700 m. Seaglider visited the offshore vertex at 47°N, 128°W, where our observations concentrated, approximately monthly. Seaglider measured temperature, conductivity, and dissolved oxygen to 1000 m and also recorded chlorophyll a (Chl a ) fluorescence and particulate optical backscatter to 150 m. Distinct interannual variation was documented in timing and depths of winter mixing, transition to a shallow summer pycnocline, and onset of mixed‐layer erosion in autumn. Chl a concentrations estimated from fluorescence were directly comparable among the seven laboratory‐calibrated sensors used, but their estimates exceeded concurrent, satellite‐derived concentrations by a factor of three. Seaglider optical profiles enabled interpretation of satellite imagery by revealing that the apparent autumn bloom after destratification was instead a vertical redistribution of phytoplankton from the subsurface maximum to a depth where they could be observed by satellites. Results of 4 yr of sampling within 25 km of the vertex demonstrate the value of gliders in ocean observing and their capability to carry out multiyear, fully autonomous operations under any sea state. The true power of glider programs will be realized in combination with other measurement platforms, including larger spatial coverage by satellites and more comprehensive biogeochemical measurements from moorings and occasional ship‐based sampling.

Observations of pigment and particle distributions in the western North Atlantic from an autonomous float and ocean color satellite - E. Boss; D. Swift; L. Taylor; P. Brickley; R. Zaneveld; S. Riser; M. J. Perry; P. G. Strutton (Limnology and Oceanography, 2008)
Profiling floats with optical sensors can provide important complementary data to satellite ocean color determinations by providing information about the vertical structure of ocean waters, as well as surface waters obscured by clouds. Here we demonstrate this ability by pairing satellite ocean color data with records from a profiling float that obtained continuous, high‐quality optical data for 3 yr in the North Atlantic Ocean. Good agreement was found between satellite and float data, and the relationship between satellite chlorophyll and floatderived particulate backscattering was consistent with previously published data. Upper ocean biogeochemical dynamics were evidenced in float measurements, which displayed strong seasonal patterns associated with phytoplankton blooms, and depth and seasonal patterns associated with an increase in pigmentation per particle at low light. Surface optical variables had shorter decorrelation timescales than did physical variables (unlike at low latitudes), suggesting that biogeochemical rather than physical processes controlled much of the observed variability. After 2.25 yr in the subpolar North Atlantic between Newfoundland and Greenland, the float crossed the North Atlantic Current to warmer waters, where it sampled an unusual eddy for 3 months. This anticyclonic feature contained elevated particulate material from surface to 1000‐m depth and was the only such event in the float's record. This eddy was associated with weakly elevated surface pigment and backscattering, but depthintegrated backscattering was similar to that previously observed during spring blooms. Such seldom‐observed eddies, if frequent, are likely to make an important contribution to the delivery of particles to depth.

Introduction to the Limnology and Oceanography Special Issue on Autonomous and Lagrangian Platforms and Sensors (ALPS) - T. D. Dickey; E. C. Itsweire; M. A. Moline; M. J. Perry (Limnology and Oceanography, 2008)
This issue is devoted to recent developments of autonomous and Lagrangian platforms and sensors (ALPS) and their uses for solving a broad range of interdisciplinary aquatic problems. The collective papers treat a variety of problems that generally require measurements spanning a continuum of temporal and spatial scales. ALPS platforms in this issue include surface drifters, profiling and other types of subsurface floats, gliders, unmanned boats, autonomous underwater vehicles, and instrumented animals. ALPS platforms can provide access in difficult environments (e.g., under ice and in high‐sea states). They are also important for emerging networked ocean and lake observing systems that require continuous measurements and near‐real‐time data. This introductory paper provides historical perspectives, background, motivation for the issue, and a tabular summary of papers in the present collection.

Monoclonal antibodies reveal changes in predator efficiency with prey spatial pattern - GEORGIANNE J. K. GRIFFITHS; COLIN J. ALEXANDER; JOHN M. HOLLAND; PETER J. KENNEDY; JOE N. PERRY; WILLIAM O. C. SYMONDSON; LINTON WINDER (Molecular Ecology, 2008)
Spatially explicit predator–prey interactions can alter the predatory potential of natural enemies augmented through conservation biological control. To test hypotheses regarding such interactions and predatory efficiency, we used a combination of molecular techniques and mark–release–recapture to study the foraging behaviour of a generalist carabid predator, Poecilus cupreus , in response to spatial patterns of its cereal aphid prey ( Metapolophium dirhodum and Sitobion avenae ). Beetle and aphid numbers were measured across two grids of sampling locations, within which aphid spatial pattern had been manipulated to generate patchy and more homogenous distributions. Aphid consumption was measured by enzyme‐linked immunosorbent assays (ELISA) of beetle gut contents, using an aphid‐specific monoclonal antibody. Movement and distribution patterns suggest that P. cupreus does not aggregate at, nor instigate prey‐taxis within, aphid patches. However, more than two‐thirds of the 2169 P. cupreus tested by ELISA had consumed aphids and the proportion of beetles containing aphid proteins was positively related to aphid density. Against expectation, the proportion of predators feeding on aphids was greatest where prey were homogenously distributed, and this was attributed to the loss of partial refuges for prey in aphid patches. The functional value of this type of uniform foraging strategy is ideally suited to early colonization of the crop habitat, when aphid numbers are low, before populations build up and form strong spatial patterns.

Comparative evaluation of 15 serological assays for the detection of syphilis infection - M. J. Cole; K. R. Perry; J. V. Parry (European Journal of Clinical Microbiology & Infectious Diseases, 2007)

Steadiness of quadriceps contractions in young and older adults with and without a history of falling - Serena F. Carville; Mark C. Perry; Olga M. Rutherford; I Christopher H. Smith; Di J. Newham (European Journal of Applied Physiology, 2007)

Strength, power output and symmetry of leg muscles: effect of age and history of falling - Mark C. Perry; Serena F. Carville; I. Christopher H. Smith; Olga M. Rutherford; Di J. Newham (European Journal of Applied Physiology, 2007)

An assessment of the suitability of a plastic thermometer screen for climatic data collection - M. C. Perry; M. J. Prior; D. E. Parker (International Journal of Climatology, 2007)
For over a century, wooden thermometer screens of the Stevenson design have been used in the meteorological station network administered by the UK Met Office. A screen is now being manufactured of the same dimensions but made from plastic. This requires minimal maintenance and has the potential for a much longer life than the wooden type. In order to determine whether a changeover to the plastic type would be acceptable for climatological applications, in particular for studies of climate change, a 12‐month trial was carried out at 3 contrasting UK locations. Temperature and relative humidity measurements were made at 1‐minute intervals in plastic and wooden trial screens installed at each site, as well as in the existing operational wooden screens. At the start of the trial, acceptance criteria based on Global Climate Observing System (GCOS) standards were set for mean and extreme temperature values. The temperature differences between the trial wooden and plastic screens were all found to be within these acceptance criteria. The largest differences occurred between pairs of wooden screens, not between wooden and plastic screens. Analysis of humidity differences between wooden and plastic screens did not yield clear results. To help understand the temperature and humidity differences, the screen data were analysed in terms of other current weather conditions, principally solar radiation and wind speed. We recommend that, in temperate climates, the plastic thermometer screen is a climatologically consistent alternative to the wooden design, requiring no adjustments to long‐term records. © Crown Copyright 2006. Reproduced with the permission of the Controller of HMSO. Published by John Wiley & Sons, Ltd.

Marcy: A chipping variety with resistance to common scab and the golden nematode - Walter S. De Jong; Donald E. Halseth; Bill B. Brodie; Keith L. Perry; Joseph B. Sieczka; Barbara J. Christ; Gregory A. Porter; Ken M. Paddock; Michael W. Peck; Robert L. Plaisted (American Journal of Potato Research, 2006)

Prefrontal and temporal gray matter density decreases in opiate dependence - In Kyoon Lyoo; Mark H. Pollack; Marisa M. Silveri; Kyung Heup Ahn; Claudia I. Diaz; Jaeuk Hwang; Seog Ju Kim; Deborah A. Yurgelun-Todd; Marc J. Kaufman; Perry F. Renshaw (Psychopharmacology, 2006)

Learning invariant object recognition in the visual system with continuous transformations - S. M. Stringer; G. Perry; E. T. Rolls; J. H. Proske (Biological Cybernetics, 2006)

The cost of being an omnivore: mandible wear from plant feeding in a true bug - Bernard D. Roitberg; David R. Gillespie; Donald M. J. Quiring; Colleen R. Alma; Wade H. Jenner; Jennifer Perry; Jason H. Peterson; Maxence Salomon; Sherah VanLaerhoven (The Science of Nature, 2005)

Proclivity and effectiveness in gall defence by soldiers in five species of gall-inducing thrips: benefits of morphological caste dimorphism in two species (Kladothrips intermedius and K. habrus) - S. P. Perry; T. W. Chapman; M. P. Schwarz; B. J. Crespi (Behavioral Ecology and Sociobiology, 2004)

Mapping of a discontinuous and highly conformational binding site on follicle stimulating hormone subunit-β (FSH-β) using domain Scan™ and Matrix Scan™ technology - Peter Timmerman; Evert Van Dijk; Wouter Puijk; Wim Schaaper; Jerry Slootstra; Stephen J. Carlisle; John Coley; Steve Eida; M. Gani; Tim Hunt; Paul Perry; Gerry Piron; et al. (Molecular Diversity, 2004)

The Effect of Overuse Activity on Achilles Tendon in an Animal Model: A Biomechanical Study - Tung-Fu Huang; Stephanie M. Perry; Louis J. Soslowsky (Annals of Biomedical Engineering, 2004)

The genetic architecture of correlations among growth‐related traits and male age at maturation in rainbow trout - C. J. Martyniuk; G. M. L. Perry; H. K. Mogahadam; M. M. Ferguson; R. G. Danzmann (Journal of Fish Biology, 2003)
Heritabilities and genetic correlations among growth‐related traits of two cultured strains (Rainbow Springs and Spring Valley) of rainbow trout Oncorhynchus mykiss were estimated using restricted maximum likelihood methods with a three‐generation pedigree. Heritability was high (>0·50 ± 0·03) for body mass and condition factor but moderate (0·35 ± 0·04) for age at sexual maturity in males. Body mass and age at sexual maturation were phenotypically correlated in the families of one experimental strain, Rainbow Springs, and had a positive genetic correlation (0·26 ± 0·03) across families from both test strains (Rainbow Springs and Spring Valley). This indicates that faster growing individuals were more likely to mature at 2 years of age than slower growing individuals in the two hatchery strains investigated. Microsatellite markers of body mass quantitative tract loci (QTL) were reconfirmed as being located on linkage groups B, G, N, 5 and new markers on Oi were detected. Some QTL effects were restricted to specific sampling dates suggesting temporal expression of QTL. QTL for condition factor were limited to linkage group G in both strains. Three suggestive QTL for precocious maturation mapped to similar regions as those for body mass in the Rainbow Springs families while no associations were evident in the Spring Valley families. The results suggest that these regions may play a role in the basis for genetic and phenotypic correlations between body mass and precocious maturation in this species.

Variation in propensity to defend by reproductive gall morphs in two species of gall-forming thrips - S. P. Perry; M. J. McLeish; M. P. Schwarz; A. H. Boyette; J. Zammit; T. W. Chapman (Insectes Sociaux, 2003)

Modelling the dynamic spatio‐temporal response of predators to transient prey patches in the field - Linton Winder; Colin J. Alexander; John M. Holland; Chris Woolley; Joe N. Perry (Ecology Letters, 2001)
The spatio‐temporal dynamics of two aphid species ( Metopolophium dirhodum and Sitobion avenae ) and a generalist predator ( Pterostichus melanarius ) were observed in a field‐scale study using a grid of 256 sampling locations with a 12‐m spacing. Using Spatial Analysis by Distance Indices we demonstrate that populations show ephemeral spatial pattern at the field scale. We observed a positive, lagged beetle response to this aphid pattern; conversely, the aphids displayed a negative, lagged response to beetle spatial pattern. Examination of the local structure of the spatio‐temporal dynamics revealed a strong response by the beetle population to aphid patches. The temporal structure of spatial associations between the species shows a strong correspondence with those from a conceptual model of predator–prey spatial interaction. The spatially coupled dynamics were sufficiently strong for the predator to have a negative effect on the intrinsic rate of increase of their prey.

Population-Based Evaluation of the Ehrlichia Ruminantium MAP 1B Indirect ELISA - Trevor F. Peter; Christopher J. O'Callaghan; Graham F. Medley; Brian D. Perry; Shalt M. Semu; Suman M. Mahan (Experimental and Applied Acarology, 2001)

Intracellular vesicular trafficking in the gill epithelium of urea-excreting fish - P. Laurent; C. M. Wood; Y. Wang; S. F. Perry; K. M. Gilmour; P. Part; C. Chevalier; M. West; P. J. Walsh (Cell and Tissue Research, 2001)

Paleogenetic evidence for a past invasion of Onondaga Lake, New York, by exotic Daphnia curvirostris using mtDNA from dormant eggs - Meghan A. Duffy; Linda J. Perry; Colleen M. Kearns; Lawrence J. Weider; Nelson G. Hairston, (Limnology and Oceanography, 2000)
Cladocerans possess traits such as resistant diapausing eggs and rapid parthenogenetic reproduction that make them efficient invaders of new habitats. Nearly all known invasions have been successful, perhaps because failed invasions are difficult to detect. It is possible, however, to identify past failed invasions, by studying the diapausing egg bank. Daphnia ephippia were found in the sediments of Onondaga Lake, New York that could neither be hatched nor identified using egg‐case morphology. Instead, we used sequences of the 12S ribosomal ribonucleic acid (rRNA) gene of mitochondrial deoxyribonucleic acid (mtDNA) extracted from diapausing eggs to identify the unknown Daphnia . We compared these DNA sequences with those generated from morphologically identified Daphnia species collected in Onondaga Lake, and with published sequences for other North American Daphnia species. The invader was identified as Daphnia curvirostris , a Eurasian species that has been only reported once before from North America, in extreme northwestern Canada. The discovery of it in Onondaga Lake signifies a greater than 4,500‐km range extension for this species. On the basis of the sediment ephippial data, D. curvirostris first appeared in the lake about 1952, reached maximum abundance during the period of peak pollution (1950s–1980s), and then essentially disappeared after 1983 when lake water quality improved. As with the finding of another exotic cladoceran, D. exilis , in Onondaga Lake (Hairston et al. 1999 a ), it is likely that chemical industry activities on the lakeshores were the original source of invading D. curvirostris , that pollution allowed this species to become established in the lake, and that the reduction in pollution ultimately led to its disappearance from the water column.

Sex differences in sensorimotor gating of the human startle reflex: all smoke? - N. R. Swerdlow; M. A. Geyer; P. L. Hartman; J. Sprock; P. P. Auerbach; K. Cadenhead; W. Perry; D. L. Braff (Psychopharmacology, 1999)

Impact of Regional Intestinal pH Modulation on Absorption of Peptide Drugs: Oral Absorption Studies of Salmon Calcitonin in Beagle Dogs - Yong-Hee Lee; Barbara A. Perry; Stacy Labruno; Hee Sang Lee; William Stern; Lisa M. Falzone; Patrick J. Sinko (Pharmaceutical Research, 1999)

Cardiovascular control via angiotensin II and circulating catecholamines in the spiny dogfish, Squalus acanthias - N. J. Bernier; K. M. Gilmour; Y. Takei; S. F. Perry (Journal of Comparative Physiology B, 1999)

Population biology of a failed invasion: Paleolimnology of Daphnia exilis in upstate New York - Nelson G. Hairston; Linda J. Perry; Andrew J. Bohonak; Meghan Q. Fellows; Colleen M. Kearns; Daniel R. Engstrom (Limnology and Oceanography, 1999)
Viable diapausing eggs of Daphnia exilis , a species within the Daphnia similis species complex, occur in sediments of Onondaga Lake, New York. The discovery of this species, which otherwise occurs exclusively in temporary saline ponds in southwestern North America, represents a range extension of 1,000 km. 210 Pb‐dating of the sediments containing diapausing eggs indicates that D. exilis was present in Onondaga Lake between the mid‐1920s and the early 1980s. The species' introduction, successful colonization, and subsequent disappearance from the water column correspond temporally with distinct events in the history of industrial activity along the shores of the lake and with the paleoecological record of this activity deposited in Onondaga Lake sediments. Only the most recently deposited diapausing eggs (late 1970s to early 1980s) hatch during laboratory incubation; older eggs may not be viable because of toxic concentrations of mercury pollution in older sediments. The D. exilis eggs that have hatched have had strikingly low genetic (allozyme) variation in comparison with the variation documented for populations in the southwestern United States by Hebert and Finston (1993). Exploration of various invasion scenarios through simulated introduction of genotypes from the southwestern United States suggests that a single genotype established the D. exilis population in Onondaga Lake. These observations document the ecological and microevolutionary patterns associated with an invasion by an exotic crustacean that currently persists only in the sediment egg bank.

Biopharmaceutical Approaches for Developing and Assessing Oral Peptide Delivery Strategies and Systems: In Vitro Permeability and In Vivo Oral Absorption of Salmon Calcitonin - Patrick J. Sinko; Yong-Hee Lee; Vijaya Makhey; Glen D. Leesman; John P. Sutyak; Hongshi Yu; Barbara Perry; Curtis L. Smith; Peidi Hu; Erik J. Wagner; Lisa M. Falzone; Laura T. McWhorter; et al. (Pharmaceutical Research, 1999)

Analyzing maps of dispersal around a single focus - S. Korie; S.J Clark; J.N Perry; M. A. Mugglestone; P .W. Bartlett; E. J . P. Marshall; J. A. Mann (Environmental and Ecological Statistics, 1998)

The effects of arginine vasotocin and catecholamines on nitrogen excretion and the cardio-respiratory physiology of the gulf toadfish, Opsanus beta - S. F. Perry; K. M. Gilmour; C. M. Wood; P. Pärt; P. Laurent; P. J. Walsh (Journal of Comparative Physiology B, 1998)

Cocaine decreases relative cerebral blood volume in humans: a dynamic susceptibility contrast magnetic resonance imaging study - M. J. Kaufman; Jonathan M. Levin; Luis C. Maas; Stephanie L. Rose; Scott E. Lukas; Jack H. Mendelson; Bruce M. Cohen; Perry F. Renshaw (Psychopharmacology, 1998)

Population structure of nuclear and mitochondrial DNA variation among humpback whales in the North Pacific - C. S. BAKER; L. MEDRANO‐GONZALEZ; J. CALAMBOKIDIS; A. PERRY; F. PICHLER; H. ROSENBAUM; J. M. STRALEY; J. URBAN‐RAMIREZ; M. YAMAGUCHI; O. VON ZIEGESAR (Molecular Ecology, 1998)
The population structure of variation in a nuclear actin intron and the control region of mitochondrial DNA is described for humpback whales from eight regions in the North Pacific Ocean: central California, Baja Peninsula, nearshore Mexico (Bahia Banderas), offshore Mexico (Socorro Island), southeastern Alaska, central Alaska (Prince Williams Sound), Hawaii and Japan (Ogasawara Islands). Primary mtDNA haplotypes and intron alleles were identified using selected restriction fragment length polymorphisms of target sequences amplified by the polymerase chain reaction (PCR–RFLP). There was little evidence of heterogeneity in the frequencies of mtDNA haplotypes or actin intron alleles due to the year or sex composition of the sample. However, frequencies of four mtDNA haplotypes showed marked regional differences in their distributions (Φ ST = 0.277; P n = 205 individuals) while the two alleles showed significant, but less marked, regional differences (Φ ST = 0.033; P n = 400 chromosomes). An hierarchical analysis of variance in frequencies of haplotypes and alleles supported the grouping of six regions into a central and eastern stock with further partitioning of variance among regions within stocks for haplotypes but not for alleles. Based on available genetic and demographic evidence, the southeastern Alaska and central California feeding grounds were selected for additional analyses of nuclear differentiation using allelic variation at four microsatellite loci. All four loci showed significant differences in allele frequencies (overall F ST = 0.043; P n = 139 chromosomes per locus), indicating at least partial reproductive isolation between the two regions as well as the segregation of mtDNA lineages. Although the two feeding grounds were not panmictic for nuclear or mitochondrial loci, estimates of long‐term migration rates suggested that male‐mediated gene flow was several‐fold greater than female gene flow. These results include and extend the range and sample size of previously published work, providing additional evidence for the significance of genetic management units within oceanic populations of humpback whales.

CDP840 - M. J. Perry; J. O’Connell; C. Walker; T. Crabbe; D. Baldock; A. Russell; S. Lumb; Z. Huang; D. Howat; R. Allen; M. Merriman; J. Walls; et al. (Cell Biochemistry and Biophysics, 1998)

The 10th Conference of the Entomological Society of Israel - Rachel Galun; I. Ishaaya; Sara Yablonski; Zmira Mendelson; Y. Mansour; Svetlana Kontsedalov; U. Pluschkell; A. R. Horowitz; A. R. Horowitz; Sara Yablonski; Zmira Mendelson; I. Ishaaya; et al. (Phytoparasitica, 1997)

Calcium binding and conformational properties of calmodulin complexed with peptides derived from myristoylated alanine-rich C kinase substrate (MARCKS) and MARCKS-related protein (MRP) - Tudor Porumb; A. Crivici; Perry J. Blackshear; M. Ikura (European Biophysics Journal, 1997)

Experimental infection of the argasid tick, ornithodoros moubata porcinus, with African swine fever virus - W. Plowright; C. T. Perry; M. A. Peirce; J. Parker (Archives of Virology, 1970)

s of papers presented at the Forty-First annual meeting - Jay L. Haddock; Ray D. Jackson; W. O. Harrington; R. L. Olson; W. J. Weston; Mary L. Belote; W. J. Hooker; A. P. Benson; R. W. Hougas; S. J. Poloquin; R. W. Ross; G. V. C. Houghland; et al. (American Journal of Potato Research, 1958)

Mechanical damage to potatoes during harvesting and handling operations in the red river valley of minnesota and North Dakota - R. E. Nylund; Perry Hemphill; J. M. Lutz; Harold Sorenson (American Journal of Potato Research, 1955)